STRATEGIES AND CHALLENGES OF SMES IN PURWAKARTA: A LITERATURE REVIEW - Sulistyanto, Tri Hadi; Wilman, Sulaeman (Universitas Multimedia Nusantara, 2025)
Abstract- This paper examines the strategies and challenges faced by Small and Medium Enterprises (SMEs) in Purwakarta, a district in West Java, Indonesia. SMEs play a crucial role in the economy, contributing to job creation and regional development. SMEs face numerous challenges that affect their growth and sustainability. The problem addressed in this paper is the limited growth and sustainability of SMEs in Purwakarta due to challenges inadequate access to financing, lack of skilled labor, and adopting modern technologies. This paper provides a novel approach by combining a literature review with text analysis using PoP (Publish or Perish) and VOSviewer for SME literatures in Indonesia. This study employs a literature review approach combined with text analysis using PoP and VOSviewer. The literature review synthesizes existing research on SMEs in Purwakarta on the strategies and challenges. VOSviewer is used to maps the relationships between key terms in SME research. SMEs face challenges in capital, infrastructure, and a lack of skilled labor. Economic factors, market fluctuations, and regulatory issues further impact their strategies. The study highlights the need for goverment support to promote sustainable growth. The literature on SMEs in Purwakarta highlights their significant economic impact on business performance, growth, and employment, with research identifying six interconnected clusters reflecting the challenges and opportunities faced by SMEs. To maximize their potential, SMEs must implement tailored strategies that enhance financial performance, market expansion, and address the unique characteristics of the local economy, infrastructure, and resources. Keywords: Challenges; Purwakarta; SMEs; Sustainability; VOSviewer